The judicialisation of politics in South Africa: A critique of the emerging trend. Issue 4 (1st October 2020) - Nyane, Hoolo
Abstract: In apartheid South Africa, the judiciary was relegated to obscurity by a combination of executive dominance and legislative supremacy. The courts of law had a very narrow function, which was to search for, and implement, the 'intention of Parliament'. This paradigm shifted with the end of apartheid. In the new dispensation, the courts have consistently held that their role has changed markedly. They are now 'stronger' than they were under apartheid's constitutional edifice. This 'stronger' position of the judiciary is indisputably in keeping with the transformative nature of the new constitutional dispensation. However, the excessive power of the judiciary also has the potential to distort the desired balance between the three key branches of government; thereby judicialising the functions of the other two political branches. The untrammelled power of the judiciary is as dangerous as a parliament that operates in terms of the doctrine of parliamentary supremacy. The purpose of this article is to critique this arguably emergent pattern of judicialisation of politics in South Africa.